Modification of identity concepts: motherland and foreigner - Patseva, Mirena; Momov, Mitko (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2015)
The paper present the part of the data of a longitudinal study of the dynamics of the lexical meaning. It is illustrated by the analysis of the concepts motherland and foreigner. Some aspects of the identity modification, since 1989 - the beginning of democratic changes in Bulgaria, are considered. Our data show change in the direction of moderate consolidation and decrease of emotional strength of reactions on a subconscious level of associations